Evaluation of Occupational Health and Safety Management System at Hospital in Indonesia - Tashia, Opy Sandra; Jamaluddin, Jamaluddin (Hasanuddin Medan, 2023)
The Haji Hospital Medan’s implementation of SMK3 is not in accordance with the Standard Regulation of the Minister of Health of the Republic of Indonesia Number 66 of 2016, where the Haji Hospital Medan still has problems implementing the Occupational Health and Safety system, and does not yet have a supervisor to supervise so that OHS-Hospital reporting and recording goes well. The researcher intends to examine the OHS-Hospital management system's inputs, processes, outputs, and outcomes at Haji Hospital Medan. The descriptive research approach was observational in nature, requiring field observations. In-depth interviews were used in qualitative research. The study's results showed that although the Haji Hospital Medan OHS-Hospital management system's input was good if there were clear SOPs and rules, the process of the OHS-Hospital management system at Haji Hospital Medan itself was not optimal because there was still a shortage of human resources in the OHS-Hospital field and a lack of concern for the OHS-Hospital program's employees. As a result, the OHS-Hospital program did not The OHS-Hospital management system at Medan Haji General Hospital has not produced the best results due to ineffective recording and reporting; as a result, many of the programs are not operating as they should. As a result, the OHS-Hospital management system at Medan Haji Hospital has become unsatisfactory. Conclusion The OHS-Hospital Management System at Haji Hospital Medan was still lacking and not fully running well. It was recommended to increase guidance and supervision so that health workers are willing to carry out the program in accordance with the SOP that has been set.